AKTIVITAS ANTIOKSIDAN TOTAL FLAVONOID DAN FENOL KULIT BATANG GAYAM (Inocarpus fagiferus Fosb) - Sri Rahayu Santi; I Made Sukadana (Jurnal Kimia (Journal of Chemistry), 2015)
These researchs aim to know of contain total flavonoid, total phenol and antioxidant activity in vitro of gayam stem bark of each extract (Inocarpus fagiferus Fosb). The result of extraction 1 kg stem bark of gayam with 8500 mL ethanol (5 x 1700 mL) to yield 30 g of concentrated extract its brown red. The partition of 15 g concentrated ethanol extract with chloroform, n-buthanol, and water to yields of 1.5g yellowish concentrated chloroform extract,  5.87 g brown red concentrated n-buthanol extract and 5.63 g concentrated water extract respectively. The result of phytochemical test of fourth extract shown that the ethanol, n-buthanol, and water extracts qualitatively contain of flavonoid and phenol compounds, while the chloroform extract only to contain phenol compound with much total flavonoid in ethanol extract 0.14 % and less at n-buthanol extract is 0.09 %. The result of antioxidant activity with DPPH method shown that water and  n-buthanol extract of gayam stem bark have value IC50 was 20 ppm smaller than  IC50 of vitamin E was 25 ppm its mean the water and  n-buthanol extract of gayam stem bark have the highest potent scavenger of free radical. The result of antioxidant activity with lipid peroxide-ammonium thiocyanate method shown the extract n-buthanol extract have the highest potent  inhibition of formed lipid peroxide (63.04%), it is higher than antioxidant activity of vitamin E (50.39%).